Obesity in Pregnancy Maternal and Fetal Outcome - Sajida Munir Siddique, Sanobar Baloch, Kanta Bai Ahuja, Rozina Mujeeb Sahito, Mir Mehrab Jan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The presence of excessive weight in mothers during pregnancy and childbirth can result in significant issues in different stages of pregnancy, delivery, postpartum and also newborn health. The aim of the present study was to examine the influence of maternal obesity on diverse consequences for both the mother and the developing baby. The main objective was to contrast the effects of obesity on outcomes during pregnancy and childbirth for overweight expectant mothers versus those with a healthy weight. Material and Methods: The investigation was carried out on pregnant women who attended the antenatal clinic at Indus Medical College Tando Muhammad Khan. The investigators utilized a sequential sampling technique and handpicked 56 cases and 56 controls. The data was analyzed using IBM SPSS 22.0 software. The chi-square test was used to identify discrepancies in proportions, while the independent t-test and ANOVA were utilized to contrast the means. They also conducted Pearson’s correlation to investigate the connection between maternal BMI and birth weight. Results: There were a total of 112 patients included in the study. There were 56 cases (patients) and 56 controls (healthy individuals). Women with gestational diabetes mellitus had a significantly higher proportion of complications compared to those without gestational diabetes mellitus (32.1% vs. 7.14%, p-value=0.02). Regarding the mode of delivery, women who underwent caesarean section had a significantly higher proportion of complications compared to those who had a vaginal delivery (37.5% vs. 62.5%, p-value=0.02). For post-partum complications, the proportion of women with postpartum fever and wound infection was very low, and no statistical comparison was made. Conclusions: The current research provided clear evidence that maternal obesity can result in negative outcomes for both the mother and fetus. In addition, the study showed that there was an increased need for induction of labor and operative interventions in women who were obese. Keywords: Fetal outcome, Maternal outcome, obesity in pregnancy